Platelet Indices and Risk of Death and Cardiovascular Events: Results from a Large Population-Based Cohort Study - Patti, Giuseppe; Di Martino, Giuseppe; Ricci, Fabrizio; Renda, Giulia; Gallina, Sabina; Hamrefors, Viktor; Melander, Olle; Sutton, Richard; Engström, Gunnar; De Caterina, Raffaele; Fedorowski, Artur (Thrombosis and Haemostasis, 2019)
Studies evaluating the relationship between platelet indices and cardiovascular (CV) outcomes yielded conflicting results. We assessed the incidence of adverse events according to baseline quintiles of platelet indices in the prospective cohort of the Malmö Diet and Cancer Study. A total of 30,314 individuals (age 57 ± 8 years) were followed for a median of 16 years (468,490 person-years). Outcome measures included all-cause death, CV death, myocardial infarction (MI), and ischemic stroke. The fifth quintile of platelet count (> 274.6 × 109/L) was associated with higher incidence of all-cause death (hazard ratio [HR] 1.20, 95% confidence interval [CI] 1.09–1.32, p < 0.001), CV death (HR 1.19, 95% CI 1.00–1.42; p = 0.044), MI (HR 1.32, 95% CI 1.12–1.54; p = 0.001), and ischemic stroke (HR 1.27, 95% CI 1.08–1.50, p = 0.004) compared with the first quintile (≤ 185 × 109/L), and also associated with a lower survival, regardless of previous history of MI (p for interaction = 0.58) or stroke (p for interaction = 0.42). In the highest quintile, history of stroke had a higher risk of CV death (HR 3.18, 95% CI 1.54–6.54) compared with no previous stroke (HR 1.12, 95% CI 0.96–1.31). The risk of MI and stroke was greatest in the fifth quintile, regardless of previous MI or previous stroke, respectively. The risk of all adverse events was similar across different quintiles of mean platelet volume. In conclusion, elevated platelet count is associated with higher mortality and risk of CV events, regardless of previous MI and stroke. Platelet count may thus be a useful marker for further stratification of CV risk, and especially of death.
Keywords: population-based; platelet count; death; cardiovascular outcome